Effects of different sources of diet on the growth, survival, biochemical composition and physiological metabolism of clam (Cyclina sinensis). (1st May 2022) - Liao, Xiaoting; Sun, Zepeng; Cui, Zhenquan; Yan, Susu; Fan, Sishao; Xia, Qing; Shi, Junjie; Ge, Hongxing; Liu, Meimei; Dong, Zhiguo
Abstract: It is essential to formulate artificial diets for Cyclina sinensis to satisfy the requirements of industrial aquaculture. We evaluated the effects of different dietary sources on the growth, survival, nutritional components, digestive performance and nonspecific immunity of C. sinensis . The diets of the three experimental groups were as follows: natural bait (control group, CG), fermented Enteromorpha prolifea (EP) compound diet (Diet #1), and fermented Pyropia yezoensis (PY) compound diet (Diet #2). Feeding these diets did not affect the individuals' final weight, specific growth rate and survival rate. The total amino acid and total monounsaturated fatty acid of individuals fed with Diet #1 were significantly higher than those provided with the other diets ( p < 0.05). There were no significant differences in the activities of α‐amylase, lipase, trypsin, total superoxide dismutase, lysozyme and acid phosphatase in the clam fed with different diets. In conclusion, the two fermented seaweed compound diets prepared herein can replace natural bait and meet the growth and developmental needs of C. sinensis . The fermented EP compound diet can improve the nutritional quality of the clam. This study lays a preliminary foundation for developing new artificial diets for clams and elucidates the further utilization of low‐value seaweed resources.